(untitled) (Comprehensive Journal of Science, 2026)
The medical profession plays a fundamental role in protecting human life; however, it is not free from the possibility of errors that may give rise to legal liability. The concept of medical error is difficult to define precisely due to the scientific and technical nature of medical practice and the fact that the physician’s obligation is limited to exercising due care rather than achieving a specific result. Medical liability arises when professional rules are breached and such breach results in harm to the patient, provided that a causal link is established. The sanctions resulting from medical error vary according to its severity and may be disciplinary or criminal in nature. This study seeks to shed light on these two forms of legal accountability, emphasizing the need to strike a balance between protecting patients and avoiding undue restrictions on the freedom of medical practice